Exploring Andalusian Scientific Output in Social Work: A Web of Science Analysis - Chaves-Montero, Alfonso (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The scientific research on social work is gaining importance in higher education. Although the incorporation of this discipline into academic research may have been delayed, it remains equally significant. Our aim in this article is to explore and analyze the current bibliographic production in the field of social education in Andalusia, mainly using the Web of Science database. The main objective of this research is to perform a bibliometric analysis of this area of knowledge, examine the indicators related to social work, and identify the strengths and weaknesses of this specific discipline.